THE STUDY OF CONSUMER ACCEPTANCE ON EEL (Monopterus albus) NUGGET WITH THE ADDITION OF YELLOW SWEET POTATO (Ipomea batatas l ) FLOUR - Adhariyah Adhariyah; Suparmi Suparmi; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT                The purpose of this research was to know the level oconsumer acceptance on eel nugget with the addition of yellow sweet potato flour. The treatment was the addition of yellow sweet potato with different amount consisting of 4 levels i.e. N0 (control), N1 (25 gr of yellow sweet potato flour), N2 (50 gr of yellow sweet potato flour), and N3 (75 gr of yellow sweet potato flour). The results showed that N2 treatment was most preferable by consumer acceptance. Whereas the organoleptic value of appearance 3.64 (74% panelists) with criteria have a golden yellow colored, aroma 3.48 (52% panelists) with spice flavor criteria, the eel meat and yellow sweet potato flour was equally specific, taste 3.51 (58% panelists) taste criteria of eel and yellow sweet potato flour was equally specific, texture 3.63 (78% panelists) have a chewy and compact criteria, and for the proximate value of moisture content 64.51%, protein content 14.73%, fat content 3.85%,  ash content 1.71%, fiber content 2.81%. It can be seen that the eel nuggets with the addition of yellow sweet potato flour was very significant effect to appearance, aroma, taste, texture, moisture, protein, fat and fiber content, but no significant effect to ash content. Keywords: Nugget, Eel, Yellow sweet potato flour